Cryptomphalus aspersa mollusc eggs extract promotes migration and prevents cutaneous ageing in keratinocytes and dermal fibroblasts in vitro. (27th October 2014) - Espada, J.; Matabuena, M.; Salazar, N.; Lucena, S.; Kourani, O.; Carrasco, E.; Calvo, M.; Rodríguez, C.; Reyes, E.; González, S.; Juarranz, A.
Synopsis Background The search of substances that minimize cutaneous ageing has increased in the last few years. Previous studies have described the regenerative properties of the secretion of the mollusc Cryptomphalus aspersa (C. aspersa) when applied topically. Objective We evaluate the in vitro effects of a new product derived from the eggs of C. aspersa, IFC‐CAF, on cell proliferation, migration, distribution of cytoskeletal proteins, production of extracellular components as well as its ability to prevent cutaneous ageing because of intrinsic or extrinsic factors (exposure to UVB) by determination of ageing markers. Methods We have used the human keratinocyte cell line (HaCaT cells), primary dermal fibroblasts (HDF) and senescent dermal fibroblasts (SHDF). The effects of the compound on cell proliferation and on the cell cycle were determined by the MTT colorimetric assay, estimation of total protein and/or trypan blue test and by flow cytometry, respectively. We also studied cell migration using the wound‐healing migration assay, whereas ELISA assays, Western Blot and immunofluorescence microscopy were carried out to test the expression of proteins related to cytoskeleton, extracellular matrix and with ageing. Results We have found that IFC‐CAF does not promote proliferation but induces migration of HaCaT, HDF and SHDF in a time‐ and dose‐dependent manner; a better organization of cytoskeletal proteins (F‐actin and vimentin) and promotes the production of extracellular components (fibronectin, collagen 1 and MMPs) and the adhesion to cell‐substrate vinculin protein. IFC‐CAF also prevents cutaneous ageing. The treatment decreases the expression of the ageing‐related markers b‐Gal, p53 and p16INK4 in SDDF cells, and improves cell survival after UVB irradiation and nuclear repair in HaCaT cells. Conclusion IFC‐CAF has regenerative properties and protects against ageing factors being, therefore, a potential therapeutic agent for treating or preventing skin ageing.